Pengaruh Ekstrak Daun Cincau Hijau (Cyclea barbata Miers) Terhadap Infeksi Bakteri Aeromonas hydrophila Pada Ikan Nila (Oreochromis niloticus) - Aristiani Rusdi Oktaviyanti; Pande Gde Sasmita Julyantoro; Dewa Ayu Angga Pebriani (Current Trends in Aquatic Science, 2020)
This study aims to determine the ability of green grass jelly leaf extract in inhibiting the growth of Aeromonas hydrophila and improving the survival of Tilapia (Oreocrhomis niloticus). This research was conducted at Fisheries Laboratory of Udayana University and UPT Laboratory of Biosciences and Biotechnology of Udayana University from May to August 2019. This experiments were use a completely randomized design (CRD) with three replications for each treatment. Antibacterial activity test was conducted in vitro with five different concentration, namely 1,25%, 2,5%, 5%, 7,5% and 10%. The challenge test was conducted in vivo with five treatments, namely A, B, C, D and E. The research showed that the green grass jelly leaf extract can inhibit the growth of Aeromonas hydrophila in vitro at the smallest concentration (1,25%) and the stronger inhibition capability at higher concentrations. Green grass jelly leaf extract also improve the survival of tilapia fish when infected by Aeromonas hydrophila in the challenge test with a higher survival rate of 76,7% compared to those without green grass jelly leaf extract addition with a survival value of only 46,7%. The quality of water measured during the study such a temperature ranging from 27,7-28?C, pH 7,2 to 7,5, and DO 5,5 to 6,7 ppm. The value of water quality is still in the optimal range for the life of Tilapia. Keywords: Extract; green grass jelly; phatogen